The Impact of Entrepreneurship on Performance In Public Sector Organizations with Application To the Egyptian Electricity Holding Company - Fahim, Marwa (The Arab Journal of Administration, 2018)
The success and prosperity of any country is directly tied to the performance of its public, private, and social voluntary sectors, separately and in combination. Governments are looking increasingly at business methods and goals for approaches to innovation, in order to achieve greater efficiency and improved performance. This paper argues that entrepreneurship is an essential alternative option to resolve inadequate government bureaucracies’ performance, particularly in developing countries. The research provides a background analysis which describes the private sector entrepreneurial activities and principles that may be transferable to the public sector. The purpose of this study is to find out the aspects (supportive organizational characteristics) and key functions of entrepreneurship in public organizations and its impact on their performance, especially in light of the controversial debate in relevant literature regarding the correlation between the two variables. Practical and empirical lessons in this research are drawn from the experience of the Egyptian Electricity Holding Company. The empirical results here – according to the executives’ views – showed that there is a significant impact of entrepreneurial activities on organizational performance of the Egyptian Electricity Holding Company, with and without considering the moderating variables, and this in spite of what is proven concerning the minimal adoption of such activities by the company. Eventually, the study proposed some managerial and administrative reforms to enhance entrepreneurship in the public sector and to improve its performance, particularly in Egypt. As well, it emphasized the importance of future public entrepreneurship research that could be conducted comparatively by taking into consideration various state-owned enterprises in multiple different countries. This will help to increase our understanding of the advantages and drivers of entrepreneurship across countries, thereby increasing the ability to generalize findings.